Os valores semânticos das condicionais e sua relação com os tempos e modos verbais - Mércia Justino, Víctor (Revista da Associação Portuguesa de Linguística, 2016)
This paper explores the relationship between tense/mood and semantic interpretation of if conditionals clauses in European Contemporary Portuguese. The data that we collected and analysed show that the correlation between tense/mood and conditionals interpretation is not necessarily biunivocal/simple: (i) there are formally subjunctive conditionals, which may convey factuality and (ii) indicative tenses and imperfect subjunctive, which may be ambiguous and compatible with three semantic classes of conditionals (factual, hypothetical and counterfactual).